Glucocorticoid resistance in acute leukemias - Styczyński, Jan (Contemporary Oncology/Współczesna Onkologia, 2003)
Glucocorticoids exert anti-inflammatory, anti-allergic, immunosuppressive and anti-proliferative activity. The clinical effect of glucocorticoids might be decreased by the development of cellular drug resistance. This phenomenon plays a role in the pathogenesis of autoimmunologic diseases, AIDS, Nelson syndrome, sclerosis multiplex and leukemias. Due to the specific lympholytic activity, glucocorticoids play a key role in the therapy of acute lymphoblastic leukemias (ALL) and lymphomas in children and adults. Laboratory and clinical aspects of the glucocorticoid role in acute lymphoblastic leukemia in children, as well as the most important mechanisms of glucocorticoid activity and cellular resistance are presented in this review. The achievement of remission in ALL is related to glucocorticoid sensitivity. The response to prednisolone monotherapy is the strongest prognostic factor in childhood ALL. The correlation of in vitro resistance to glucocorticoids with short- and long-term results of the antileukemic therapy was shown in retrospective and prospective studies. The resistance to glucocorticoid monotherapy in childhood ALL is related to 100-fold higher in vitro prednisolone resistance. The age and immunophenotype correlate with in vitro glucocorticoid resistance. Lymphoblasts on relapse are highly resistant; the difference is higher for glucocorticoids than for other drugs. Lymphoblasts from adults, when compared to children, present higher glucocorticoid resistance. Putative mechanisms of glucocorticoid resistance include abnormalities in the drug diffusion through the cell membrane; low number, variants and dysfunction of glucocorticoid receptors in cytoplasm; no activation of the glucocorticoid-receptor complex, its translocation to the nucleus, binding to DNA and DNA fragmentation; DNA repair; disregulation of the receptor or mitochondrial apoptotic pathway and resistance to apoptosis.